ANALISIS PERSONAL HYGIENE DAN KONDISI SANITASI NARAPIDANA PADA LAPAS KLAS IIB CIANJUR - irman raka (MOTORIK Jurnal Ilmu Kesehatan, 2020)
A healthy environment is an ecological balance that must exist between humans and the environment in order to guarantee a healthy condition of humans. This study aims to determine how the state of personal hygiene and sanitary conditions contained in Cianjur Class II Prison. This research was conducted in the form of qualitative research with phenomenological approach, namely by conducting interviews with 10 informants, where 2 main informants were interviewing the polyclinic and casibinadik health workers. The research was conducted from 29 January to 25 February 2020 in Lapas IIB Cianjur. The results of the study showed the results of the analysis related to personal hygiene conditions and sanitary conditions of prisoners in Prison Class IIB Cianjur can be concluded that in terms of personal hygiene in each individual prisoner is already good in hand and nail hygiene, cleanliness of clothes, towels and cleanliness of his bed. And in terms of sanitation, clean water, rubbish and latrines are good enough and cleanliness is always maintained by them by organizing a daily picket system in maintaining the cleanliness of the rooms in each block. The author suggests to Cianjur Class IIB Lapas officers to further increase supervision on each supervision of cleanliness in each block, and conduct health education for personal hygiene and sanitation environment sanitation to increase awareness of prisoners that hygiene must always be maintained so that they are not susceptible to disease.